Financing by the Encashment of Trade Receivables through Trade Receivable Exchange in Bangladesh - Md. Moniruzzaman; Dato’ Dr. Mohd Padzil Hashim; Dr. Annuar Md Nassir (Asian Journal of Finance & Accounting, 2024)
A large amount of money in the economy remains in the form of trade receivables that are created from the business to business (B2B) transactions among the firms. There are 7.818 million firms in Bangladesh and 99% of them are in the categories of cottage, micro, small, and medium enterprises (CMSMEs). They supply the raw materials, semi-finished goods, and services on credit to the large and blue-chip corporate manufacturers. CMSMEs generally wait for a period of 30 days, 60 days, 90 days and so on for the payment. During this period, CMSMEs suffer from the lack of working capital that remains tied in trade receivables against their credit sales to the corporate buyers. The study provides a financing solution through trade receivable exchange (TRX) to release the fund into cash from the investment locked into trade receivables. The study presents the concept and modus operandi of TRX. It shows the global practice of TRX. It assesses the application of TRX in the context of Bangladesh and in doing so; it has explored market space, readiness, FinTech industry, and stakeholders related to TRX. The academic research on TRX in Bangladesh is rare that presents a research gap for the study. Here, around 51% CMSMEs close their business for the shortage of working capital. The study addresses this working capital problem through TRX that brings a novelty and significance for the research.